The budget and budgetary law of the Polish People’s Republic - Duda-Hyz, Michalina (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
In Polish People’s Republic, as in other socialist countries, the budget system and the organisational structure of the budget corresponded to the assumptions of the political and socio-economic system of the socialist State. This means that the principles of the management of the budget and budgetary law itself were significantly different from the principles and norms then in force in Western European countries. The aim of this article is to outline how the main stages of the Polish People’s Republic’s budget were forming, as well as to demonstrate the impact of changing tendencies to centralise and decentralise the economy on the structure of the State budget. The first part of the article is devoted to the presentation of the process of adaptation and adjustment of the inter-war fiscal legislation to the new political and economic situation. In the second part, the main phases of the reconstruction of the budgetary system have been analysed. The next two parts of the article refer to the issues of adjustment of the budget system to the decentralisation of the management of the national economy and to the crisis of the early 1980s. The implementation of the research objectives made it possible to formulate the thesis that, despite the changing tendencies towards centralisation and decentralisation, throughout the entire period of the Polish People’s Republic the budget system and the organisational structure of the budget itself corresponded in principle to the assumptions of the political and socio-economic system, at the basis of which lay the principle of democratic centralism and the political and economic unity of the State.
Keywords: state budget; budgetary law; budgetary system; Polish People’s Republic; democratic centralism; autoritarianism; socialist state